CD4+CD25HiFoxP3+ regulatory T cells in long‐term cardiac xenotransplantation. (17th December 2017) - Singh, Avneesh K.; Chan, Joshua L.; Seavey, Caleb N.; Corcoran, Philip C.; Hoyt, Robert F.; Lewis, Billeta G.T.; Thomas, Marvin L.; Ayares, David L.; Horvath, Keith A.; Mohiuddin, Muhammad M.
Abstract: Background: CD4+CD25 Hi FoxP3+ T (Treg) cells are a small subset of CD4+ T cells that have been shown to exhibit immunoregulatory function. Although the absolute number of Treg cells in peripheral blood lymphocytes (PBL) is very small, they play an important role in suppressing immune reactivity. Several studies have demonstrated that the number of Treg cells, rather than their intrinsic suppressive capacity, may contribute to determining the long‐term fate of transplanted grafts. In this study, we analyzed Treg cells in PBL of long‐term baboon recipients who have received genetically modified cardiac xenografts from pig donors. Methods: Heterotopic cardiac xenotransplantation was performed on baboons using hearts obtained from GTKO.hCD46 (n = 8) and GTKO.hCD46.TBM (n = 5) genetically modified pigs. Modified immunosuppression regimen included antithymocyte globulin (ATG), anti‐CD20, mycophenolate mofetil (MMF), cobra venom factor (CVF), and costimulation blockade (anti‐CD154/anti‐CD40 monoclonal antibody). FACS analysis was performed on PBLs labeled with anti‐human CD4, CD25, and FoxP3 monoclonal antibodies (mAb) to analyze the percentage of Treg cells in six baboons that survived longer than 2 months (range: 42‐945 days) after receiving a pig cardiac xenograft. Results: Total WBC count was low due to immunosuppression in baboons who received cardiac xenograft from GTKO.hCD46 and GTKO.hCD46.hTBM donor pigs. However, absolute numbers of CD4+CD25 Hi FoxP3 Treg cells in PBLs of long‐term xenograft cardiac xenograft surviving baboon recipients were found to be increased (15.13 ± 1.50 vs 7.38 ± 2.92; P  < .018) as compared to naïve or pre‐transplant baboons. Xenograft rejection in these animals was correlated with decreased numbers of regulatory T cells. Conclusion: Our results suggest that regulatory T (Treg) cells may contribute to preventing or delaying xenograft rejection by controlling the activation and expansion of donor‐reactive T cells, thereby masking the antidonor immune response, leading to long‐term survival of cardiac xenografts.